How we provide thawed plasma for trauma patients. Issue 8 (27th May 2015) - Stubbs, James R.; Zielinski, Martin D.; Berns, Kathleen S.; Badjie, Karafa S.; Tauscher, Craig D.; Hammel, Scott A.; Zietlow, Scott P.; Jenkins, Donald
<x xml:space="preserve">Abstract</x> Almost 50% of trauma‐related fatalities within the first 24 hours of injury are related to hemorrhage. Improved survival in severely injured patients has been demonstrated when massive transfusion protocols are rapidly invoked as part of a therapeutic approach known as damage control resuscitation (DCR). DCR incorporates the early use of plasma to prevent or correct trauma‐induced coagulopathy. DCR often requires the transfusion of plasma before determination of the recipient's ABO group. Historically, group AB plasma has been considered the "universal donor" plasma product. At our facility, the number of AB plasma products produced on an annual basis was found to be inadequate to support the trauma service's DCR program. A joint decision was made by the transfusion medicine and trauma services to provide group A thawed plasma (TP) for in‐hospital and prehospital DCR protocols. A description of the implementation of group A TP into the DCR program is provided as well as outcome data pertaining to the use of TP in trauma patients.